Welfare reform: an exploration of devolution - Pandey, Shantanu (Social justice, 2001)
Part of a special issue on welfare and punishment in the era of President George W. Bush. The devolution of power to administer social programs and services in the U.S. from the federal to state and local government has proved to be a divisive issue. Supporters argue that governmental units closer to the people are more knowledgeable about and better positioned to respond to people's needs; opponents contend that devolution is based on inaccurate premises and will hurt the poor and the nation.